Pengaruh Media Sosial dan Fasilitas Terhadap Minat Kunjungan Wisatawan Pantai Menganti di Kabupaten Kebumen - Utami, Ayu Cahyaning; Subeni, Fajar (CV. Kurnia Grup, 2025)
The aim of this research is to explore the influence of certain factors on tourists' decisions in choosing Menganti Beach as their holiday destination. This research aims to explore the influence of promotions carried out through social media and the quality of facilities on visitors' interest in enjoying the beauty of Menganti Beach in Kebumen Regency. To find out the extent of the influence of promotions on social media and the quality of facilities at Menganti beach on tourists' interest in visiting this beach destination. In this research, a quantitative research method was chosen which involved various data collection techniques, such as the use of questionnaires for visitors to Menganti Beach, interviews with managers, direct observation by researchers, as well as the use of literature studies that had been carried out previously. In this study, we took a sample of 100 individuals to represent the population. Data analysis was carried out using descriptive statistical methods to describe the characteristics of the objects studied through the sample and population. Carrying out regression analysis to investigate the influence of one variable on another, also known as factor analysis. This research has broadened our insight into the elements that influence tourists' interest in exploring beach destinations. Apart from that, this research also provides recommendations to the parties involved to improve promotional strategies on social media and Menganti Beach facilities to attract more visitors.